Preliminary Amplification Studies of Some Sites using Different Earthquake Motions - Bhutani, Manish; Naval, Sanjeev (Civil Engineering Journal, 2020)
Stability of infrastructure during earthquakes demands ground response analysis to be carried out for a particular region as the ground surface may suffer from amplified Peak Ground Acceleration (PGA) as compared to bedrock PGA causing instability. Many studies have been carried out the world over using different techniques but very few studies have been carried out for the northern part of India, Punjab situated at latitude of 31.326° N and longitude of 75.576° E, which is highly seismic and lies in seismic zone IV as per IS:1893-2016. In this paper 1-D equivalent non-linear ground response analysis has been conducted for sixteen sites of Jalandhar region, Punjab (India) by using five earthquake motions. Input ground motions are selected from the worldwide-recorded database based on the seismicity of the region. Based on the average SPT-N values, all the sites have been classified as per the guidelines of National Earthquake Hazard Reduction program (NEHRP). Shear modulus (G) was calculated using correlation between G and SPT–N Value. The ground surface PGA varies from 0.128 to 0.292 g for the sites of Jalandhar region with Amplification Factor values varying from 1.08 to 2.01. Hence the present study will be useful to the structural designers as an input towards suitable earthquake resistant design of structures for similar sites.